2000
DOI: 10.1161/01.str.31.4.834
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Computed Tomographic–Guided Aspiration and Thrombolysis of Intracerebral Hematoma

Abstract: Background and Purpose-We review preliminary experience with patients harboring intracerebral hematoma (ICH) treated by stereotactic computed tomographic (CT) guided thrombolysis and aspiration and assess procedure feasibility and safety. Methods-Twelve patients with supratentorial ICH Ն25 mL without suspected underlying structural etiology or coagulopathy and an initial Glasgow Coma Scale (GCS) score of Ն5 were treated. A catheter was directed stereotactically or manually into the ICH through a burr hole un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 36 publications
1
71
1
1
Order By: Relevance
“…[13][14][15][16]28 A number of these models have been demonstrated as highly accurate in predicting long-term outcome, and this finding has led to the use of GCS score and ICH hematoma volume as enrollment criteria for various studies of intervention in ICH. 7,8,29 However, several of these models use complex algebraic equations in outcome prediction, and none have been simplified into a standard clinical grading scale analogous to the GCS, NIHSS, Hunt-Hess, WFNS, or Spetzler-Martin scales. It is likely that this lack of a uniform ICH scale has contributed to variability in enrollment criteria for ICH studies as well as to heterogeneity in clinical ICH care.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16]28 A number of these models have been demonstrated as highly accurate in predicting long-term outcome, and this finding has led to the use of GCS score and ICH hematoma volume as enrollment criteria for various studies of intervention in ICH. 7,8,29 However, several of these models use complex algebraic equations in outcome prediction, and none have been simplified into a standard clinical grading scale analogous to the GCS, NIHSS, Hunt-Hess, WFNS, or Spetzler-Martin scales. It is likely that this lack of a uniform ICH scale has contributed to variability in enrollment criteria for ICH studies as well as to heterogeneity in clinical ICH care.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of several case series have reported encouraging results when using stereotactic aspiration with fibrinoly-sis. 77,87,88,93,110 Doi, et al, 32 from Japan were the first to use stereotactic aspiration with a hematoma lysis method. Successful use of both urokinase and recombinant tPA has been reported.…”
Section: Neurosurg Focus / Volume 15 / October 2003mentioning
confidence: 99%
“…Importantly, HyStem-HP's use is congruent with current stroke therapy procedures since it can be administered via a catheter or cannula through a burr hole using computed tomographic (CT) guidance (Montes, et al, 2000).…”
Section: Strokementioning
confidence: 99%